PENGARUH RETURN ON ASSET (ROA), DEBT RATIO (DER), PERPUTARAN PERSEDIAAN DAN PERPUTARAN MODAL KERJA TERHADAP LIKUIDITAS PERUSAHAAN PERDAGANGAN (STUDI PERUSAHAAN PERDAGANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE TAHUN 2019 – 2022) - Fatahillah, Tajib; Andini, Rita; Lestari, Utami Puji (STIE Semarang, 2024)
This research aims to determine the effect of Return on assets, Debt to equity ratio, Inventory Turnover and Working Capital Turnover on Liquidity using the Current Ratio measuring tool in trading companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2022 period. This research uses a quantitative approach, the population in this research is 48 trading companies. Through a purposive sampling technique, a sample size of 25 companies was obtained which was adjusted to the research criteria. The data analysis techniques used are descriptive statistics, model testing and hypothesis testing using multiple linear regression analysis. The research results show that Return On Assets (ROA) has a positive and insignificant influence on liquidity. Debt To Equity Ratio (DER) has a negative and significant influence on liquidity. Inventory Turnover has a negative and significant influence on liquidity. Working Capital Turnover has a negative and significant influence on liquidity.